2007
DOI: 10.1017/s1461145707007857
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor-deficient mice exhibit a hippocampal hyperserotonergic phenotype

Abstract: Growing evidence supports the involvement of brain-derived neurotrophic factor (BDNF) in mood disorders and the mechanism of action of antidepressant drugs. However, the relationship between BDNF and serotonergic signalling is poorly understood. Heterozygous mutants BDNF +/x mice were utilized to investigate the influence of BDNF on the serotonin (5-HT) system and the activity of the serotonin transporter (SERT) in the hippocampus. The zero net flux method of quantitative microdialysis revealed that BDNF +/x h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 51 publications
5
59
1
Order By: Relevance
“…The parameter most commonly used to assess stimulated microdialysis data is area under the curve (AUC). 3,7,17,29,32 High-K + -induced serotonin overflow peak heights and slopes were also analyzed. 33 Serotonin overflow in response to the shortest 1 min high-K + pulse was detected in all WT-M subjects, whereas 4/5 mice in both the WT-F-PE and WT-F-MD groups exhibited detectable serotonin overflow.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameter most commonly used to assess stimulated microdialysis data is area under the curve (AUC). 3,7,17,29,32 High-K + -induced serotonin overflow peak heights and slopes were also analyzed. 33 Serotonin overflow in response to the shortest 1 min high-K + pulse was detected in all WT-M subjects, whereas 4/5 mice in both the WT-F-PE and WT-F-MD groups exhibited detectable serotonin overflow.…”
Section: Resultsmentioning
confidence: 99%
“…However, typical serotonin microdialysis sampling in vivo is on the order of 10−30 min. [2][3][4][5][6][7]10 When coupled with offline analysis, resolution as high as 2 min has been achieved for serotonin sampling. 14−18 Offline approaches often involve decreased throughput, however, due to longer analysis times.…”
mentioning
confidence: 99%
“…Although the effects of intracerebroventricular BDNF on 5-HT clearance arose 3 days after growth factor injection, intrahippocampal injections led to reductions in clearance within 30 minutes, suggesting engagement of rapid, posttranslational mechanisms. Interestingly, reported reduced rates of 5-HT clearance in vivo using amperometric recordings of aged mice genetically deficient for BDNF (BDNF+/2 animals) that did not correlate with changes in SERT density (although see Guiard et al, 2008, where density changes were observed), suggestive of functional modulatory pathways connecting neurotrophin and transporter, although perhaps indirect. Although clearly complexities remain in terms of how BDNF modulates SERT over time scales of minutes to months, the relationship of the BDNF/TrkB pathway and SERT function to depression and antidepressant mechanisms points to the translational potential of further studies of this interconnection (Haase and Brown, 2015).…”
Section: B Evidence For Endogenous Pathways Triggering Regulation Ofmentioning
confidence: 99%
“…[192][193][194] Work with mouse lines characterized by deficient Bdnf has shown that these trophic effects are important for normal serotonergic neurotransmission. [195][196][197][198][199][200] In addition, several lines of evidence have provided support for a role of Mecp2 in the regulation of activity-dependent transcription of Bdnf, 134,201,202 suggesting that alterations in 5-HT signaling could arise from deficient Mecp2 function, through dysregulation of Bdnf. Bdnf-null mice die soon after birth, but mutants have been developed with conditional disruption of Bdnf, limited to either the prenatal or postnatal period.…”
Section: Autism Candidate Genes and Synaptic Functionmentioning
confidence: 99%
“…Interestingly, heterozygous mice with one null Bdnf allele have decreased function of the serotonin transporter in hippocampus. 195,197 Murphy et al, [208][209][210] in a series of informative studies on gene interactions, showed that deficits in Sert nulls were exacerbated when mice were bred with Bdnf heterozygous animals. Male offspring had much greater susceptibility for the more severe phenotype than female mice.…”
Section: Autism Candidate Genes and Synaptic Functionmentioning
confidence: 99%